Association between caffeine intake and erectile dysfunction: a meta-analysis of cohort studies - Mehdi Karimi; Omid Asbaghi; Kimia Kazemi; Fatemeh Maleki Sedgi; Ensiye Soleimani; Hanieh Keikhay Moghadam (BMC, 2024)
Abstract Background Erectile dysfunction (ED) is a common condition with various contributing factors, including lifestyle and dietary habits. Caffeine, a widely consumed stimulant, has been linked to multiple physiological effects on vascular function and hormonal balance that might influence sexual function. This meta-analysis aims to evaluate the association between caffeine intake and the risk of ED by analyzing data from cohort studies. Methods A systematic search was conducted across PubMed, Web of Science, Scopus, and Embase databases, and a manual search was conducted on Google Scholar for studies on the relationship between caffeine intake and ED in adult men. The search included observational studies published up to April 1, 2024. Four cohort studies were included, and their data were extracted and analyzed by STATA version 18. Results Four included cohort studies comprised 51,665 cohort members. The study population included adult males, on average, aged 18 to 80. The results indicate that there was no significant relationship between coffee consumption and the risk of ED (relative risk [RR] = 0.94, 95% CI: 0.86-1.03; p = 0.999). Conclusions The current evidence suggests no significant relationship between caffeine intake and ED, but limited studies limit conclusions. Future research should focus on larger sample sizes, standardized outcome assessments, and different dosages and forms of caffeine consumption.